2013
DOI: 10.1016/j.expneurol.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Long distance directional growth of dopaminergic axons along pathways of netrin-1 and GDNF

Abstract: Different experimental and clinical strategies have been used to promote survival of transplanted embryonic ventral mesencephalic (VM) neurons. However, few studies have focused on the long-distance growth of dopaminergic axons from VM transplants. The aim of this study is to identify some of the growth and guidance factors that support directed long-distance growth of dopaminergic axons from VM transplants. Lentivirus encoding either glial cell line-derived neurotrophic factor (GDNF) or netrin-1, or a combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 70 publications
(87 reference statements)
2
29
0
Order By: Relevance
“…We observed that post-injury induction of caErbB2 similarly stimulates SCs in injured DRs to proliferate and form processes and delays their re-dedifferentiation. Our findings are consistent with the notion that NRG-1/ErbB signaling may initiate SC dedifferentiation after injury (C. Zhang et al, 2013;Lee et al, 2014).…”
Section: Discussion Caerbb2 Induction and Denervated Scssupporting
confidence: 82%
See 2 more Smart Citations
“…We observed that post-injury induction of caErbB2 similarly stimulates SCs in injured DRs to proliferate and form processes and delays their re-dedifferentiation. Our findings are consistent with the notion that NRG-1/ErbB signaling may initiate SC dedifferentiation after injury (C. Zhang et al, 2013;Lee et al, 2014).…”
Section: Discussion Caerbb2 Induction and Denervated Scssupporting
confidence: 82%
“…Replication deficient lentiviruses encoding either chABC (LVchABC) or GDNF (LV-GDNF) used a pBOB lentiviral expression vector with CMV-enhanced chicken ␤-actin (CAG) promoter. The procedures to generate the viruses and their efficacy were described previously; LVchABC (Curinga et al, 2007;Jin et al, 2011) and LV-GDNF (L. Deng et al, 2013;C. Zhang et al, 2013;Kelamangalath et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its action on DA neuron survival, GDNF also stimulates outgrowth of DA neurons after lesion or grafting in the rodent (Sinclair et al, 1996;Sautter et al, 1998;Wilby et al, 1999;Zhang et al, 2013) and NHP brain Redmond Jr. et al, 2009;Wakeman et al, 2014). Combination of GDNF and NETRIN-1 was found to support directed long-distance growth of DA axons from rodent fVM grafts .…”
Section: Axonal Outgrowth and Migration In The Host Brainmentioning
confidence: 97%
“…These GABAergic transplants into the nigra also may contribute benefit by increasing the local suppression of noise as described previously for the seemingly noisy striatum. As efforts expanded, it became clear that considerable neurotrophic support was necessary and this was either provided by "bridge" tissue grafts that might be likely to release such compounds, such as Schwann cell type cells, or the local cells were induced to release these compounds by viral transgenic expression (e.g., [82,160,170]). This strategy renders the CNS territory through which the new dopaminergic fibers must grow more hospitable, presumably also providing retrograde support signals, inspiring continued growth, and staving off the previously-described cell death that results from the lack of connectedness during this growth journey.…”
Section: Adaptation Of Transplanted Neural Cells To the Endogenous Homentioning
confidence: 99%